Dealing With Conflicting Values in Policy Experiments: A New Pragmatist Approach. Issue 9 (October 2022) - Oldenhof, Lieke; Wehrens, Rik; Bal, Roland
Despite the "turn to values" in Public Administration, there is still a lack of empirical research in situ that investigates how various stakeholders in interaction develop strategies to deal with conflicting values over time. By using a new pragmatist approach, this article fills in this gap by investigating policy experiments in Dutch healthcare. The results show how professionals, citizens, and policymakers differently valued the worth of policy experiments, which manifested itself in multiple value conflicts. To deal with these conflicts, stakeholders adopted different strategies: colonization, compromising, prioritization, short-cutting, organizational enmeshing, and pilotification. The results show a shift from exclusive top-down strategies to inclusive multi-value strategies over time.